The Effectiveness of Employee Performance on the Satisfaction of BPJS Participants in Obtaining Social Security Funds - Sonia Purba (Journal of Indonesian Management, 2022)
Currently, many businesses in the production sector are being developed by the community. Many companies take advantage of the performance of employees to support the quality of production and meet the target market. The need for Human Resources (HR) must be supported by the quality of granting rights in accordance with the level of employees that have been determined by the government. Policies that have been set by the government to be implemented for companies with a certain number of employees must be complied with. This is an effort to give employees the right to work. The purpose of this study was to determine the effectiveness of employee performance on obtaining social security funds in the form of BPJS. The research method used includes qualitative research. The data collection technique used is observation and interview technique, while the data analysis technique used includes the thoughts of Miles and Huberman, namely data reduction, data presentation and conclusion drawing.